Using the Decision-Ade™ Segmentation Strategy to Better Understand Extension Audiences - Randall A. Cantrell; Laura Warner; Joy Rumble; Alexa Lamm (EDIS)
Decision-Ade™ is a tool Extension can use to better understand how residents with a range of household budgets feel about their utility bills. Analyzing households in terms of both income and utility bill “botheredness” creates a more comprehensive picture of that household’s utility use and its willingness to modify utility consumption relative to other households. This 5-page fact sheet uses survey data of Florida residents to demonstrate the insights Decision Ade™ can provide and how those insights can inform Extension programming. Written by Randall Cantrell, Laura Warner, Joy Rumble, and Alexa Lamm, and published by the UF Department of Family, Youth and Community Sciences, July 2015.